2013
DOI: 10.1021/ac402459h
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Based, Sedimentation-Assisted Plasma Separator for Point-of-Care Applications

Abstract: Often, high sensitivity, point of care, clinical tests, such as HIV viral load, require large volumes of plasma. Although centrifuges are ubiquitously used in clinical laboratories to separate plasma from whole blood, centrifugation is generally inappropriate for on-site testing. Suitable alternatives are not readily available to separate the relatively large volumes of plasma from milliliters of blood that may be needed to meet stringent limit-of-detection specifications for low abundance target molecules. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 42 publications
1
119
0
Order By: Relevance
“…Liu et al reported on a simple-to-use and lowcost membrane-based sedimentation-assisted plasma separator capable of separating a relatively large volume of plasma from undiluted whole blood within minutes (26). A novel microfluidic blood filtration element (BFE) that extracts plasma from whole blood in less than 10 min was demonstrated by Homsy et al to be suitable for clinical application (27), and the use of red blood cell (RBC) agglutination for separating plasma from finger-prick volumes of whole blood directly in microfluid paper is also possible (28).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported on a simple-to-use and lowcost membrane-based sedimentation-assisted plasma separator capable of separating a relatively large volume of plasma from undiluted whole blood within minutes (26). A novel microfluidic blood filtration element (BFE) that extracts plasma from whole blood in less than 10 min was demonstrated by Homsy et al to be suitable for clinical application (27), and the use of red blood cell (RBC) agglutination for separating plasma from finger-prick volumes of whole blood directly in microfluid paper is also possible (28).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, the proposed design shows its potential as a clinical tool compared to previous works. Firstly, the initial volume of the required sample, 5µL, is considerably reduced compared to the former works [34,38]. Secondly, the volume of the extracted blood plasma, 0.1 µL, is enough to implement the TSH test and also is more than the obtained volume in the previous filter designs [33,35].…”
Section: Integration Of Plasma Separation With Analyte Detection For mentioning
confidence: 99%
“…More recently, in 2013 a pump-free and membrane-based blood plasma separator is reported by Liu et al [38]. Gravitational sedimentation and filtration techniques were combined for nucleic acid amplification and HIV detection.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for blood filtration the small reagent volume needed in microfluidic systems is beneficial compared to conventional diagnostic devices in centralized facilities [2]. To separate plasma from whole blood different concepts were introduced such as special filter materials [3], designed filtration channels [2,4], or separation via a membrane [5]. Combining microfluidic concepts with a biosensor results in compact, decentralized, and fast operating devices [6,9].…”
Section: Introductionmentioning
confidence: 99%